Inflation as a fiscal limit - Francesco Bianchi; Leonardo Melosi (Federal Reserve Bank of Chicago, 2022)
Low and stable inflation requires an appropriate fiscal framework aimed at stabilizing government debt. Historically, trend inflation is critically influenced by actual or perceived changes to this framework, while cost-push shocks only account for short-lasting movements in inflation. Before the pandemic, a moderate level of fiscal inflation has counteracted deflationary pressures, helping the central bank to avoid deflation. The recent fiscal interventions in response to the COVID pandemic have altered the private sector's beliefs about the fiscal framework, accelerating the recovery, but also determining an increase in fiscal inflation. This increase in inflation could not have been averted by simply tightening monetary policy. The conquest of post-pandemic inflation requires mutually consistent monetary and fiscal policies to avoid fiscal stagflation.
Keywords: E50; E62; E30; 330; Fiscal limits; monetary/fiscal policy mix; inflation; government debt; fiscal stagflation